El compañero Durruti hablando en Santa Cruz de Tenerife al regreso de su destierro en Fuertebentura el año 1932 (1932)
El compañero Durruti hablando en Santa Cruz de Tenerife al regreso de su destierro en Fuertebentura el año 1932.